IMPLEMENTASI ALGORITMA K-MEANS CLUSTERING PADA APLIKASI MOBILE BANKING BANK SAMPAH KELUARAHAN TUAH MADANI KOTA PEKANBARU - Gusrio Tendra; Jean Riko Kurniawan Putra; Rindi Johan (J-Icon : Jurnal Komputer dan Informatika, 2021)
Tuah Madani Village has made the Waste Bank program as part of an effort to help improve the welfare of the community. With the existence of a waste bank, in addition to channelling waste money, the community can also generate savings from the waste that is deposited. The existence of a waste bank will make it easier for the village to collect data on areas that produce the amount of waste and require more attention in handling the waste. At this time the process of calculating community waste deposits by the waste bank is still done manually in a deposit book, as well as the grouping of areas that become waste producers is difficult to do because the recording of waste deposit data is only done in one book, where if the waste bank wants to alculate the waste deposit in an area, it must be done manually and one by one and then amount the deposit amount, of course it takes a long time and has a low level of accuracy. The purpose of this study is to implement the K-Means Clustering Algorithm in order to facilitate the process of grouping areas based on the type of waste generated by each neighbourhood unit/housing registered in the Tuah Madani village. Garbage bank applications can group categories based on data on waste deposits made by the community, and with this data it can help the village to coordinate janitors and waste transport fleets.